PERAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) DALAM MENGEMBANGKAN KARAKTER SISWA SMK AL-MUHTADIN - Latifah Isfuliah; Nasichah; Wanda Latifah; Ahmad Rizki (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This article was written using the meta-analysis method. With the type of research used qualitatively. This study was used to determine the extent to which character education was carried out in Senior High School (SMA) learning. Seeing the advancing times, many children lack good morals, and social in social life. At this time, character education is needed to form the next generation of a qualified, superior, and dignified nation by fostering a sense of responsible attitude in facing this era of globalization. Character education can be optimized in the development of children's dimensions cognitively. Physical. Social-emotional, creative, and spiritual. This character education aims to form and build Indonesian people who are devoted to God Almighty, obey all applicable legal rules, and interact between cultures and tribes. Applying the noble values of the nation's culture, and strengthening and instilling in oneself the spiritual, moral, and ethical foundation of an Indonesian nation. Law number 20 of 2003 concerning the National education system article 3, aims to educate the nation's life and serves to shape the character or characteristics of the Indonesian Nation. Student character building at school can be done through routine and spontaneous activities to shape children to perform good and positive behavioral values.